Optimasi Unit Desalinasi Air Laut dengan Alat Seawater Reverse Osmosis (Membran) pada Unit PLTU Sulbagut I Gorontalo Mengunakan Metode Pendekatan Response Surface I-Optimal Design Expert - Imaruzi, Nashru; Zulkifli, Zulkifli; Rihayat, Teuku (Jurnal Teknologi, 2024)
Indonesia is still experiencing an energy crisis. One of the efforts that has been made by the Government is to build various new power generation facilities and optimize existing power plants. As for the PLTU cycle, demineralized water is required to be obtained from fresh water, so the role of a desalination plant is needed to provide fresh water. This project was to evaluate and optimize the role of the seawater desalination units using seawater reverse osmosis membrane devices at the Sulbagut I Gorontalo PLTU unit using the response surface I-optimal design expert approach. Optimization of seawater desalination work is carried out by observing the reverse osmosis membrane process in the desalination unit. The main equipment involved in the desalination process is the reverse osmosis membrane module, SWRO high pressure pump, turbo charger energy recovery device, chlorine reductant and antiscalant dosing. The working principle of desalination optimization is analysis using formulations and graphics from Design Expert with the I-Optimal Response Surface method with observational data using actual operating conditions. Analysis and testing of the model condition results obtained from the design expert, with the model analysis results obtained a set up goal will be carried out with the maximum parameters of the production parameters which get optimization results in the form of membrane inlet pressure at a set point of 4,938 MPa which is the best and most efficient and optimal optimization result where this parameter is applied to get optimal production results in quality and quantity.